Supplementation with Brazil nuts and green tea extract regulates targeted biomarkers related to colorectal cancer risk in humans - Hu, Ying; McIntosh, Graeme H.; Le Leu, Richard K.; Somashekar, Roshini; Meng, Xing Q.; Gopalsamy, Geetha; Bambaca, Libby; McKinnon, Ross A.; Young, Graeme P. (British journal of nutrition, 2016)
Se and green tea have been shown in epidemiological, observational and preclinical studies to be inversely related to the risk of developing colorectal cancer (CRC). However, there are limited studies to evaluate their regulatory effects on genes/proteins that relate to CRC oncogenesis in human subjects, such as selenoproteins, WNT signalling pathway, inflammation and methylation. This study examined the effects of supplementation of Se using Brazil nuts and green tea extract (GTE) capsules, alone and in combination, on targeted biomarkers. In total, thirty-two volunteers (>50 years of age) with plasma Se≤1·36 µmol/l were randomised to one of three treatment groups: nine to Se (approximately 48 µg/d) as six Brazil nuts, eleven to four GTE capsules (800 mg (-)-epigallocatechin-3-gallate) and twelve to a combination of Brazil nuts and GTE. Blood and rectal biopsies were obtained before and after each intervention. Plasma Se levels, rectal selenoprotein P (SePP) and β-catenin mRNA increased significantly in subjects consuming Brazil nuts alone or in combination, whereas rectal DNA methyltransferase (DNMT1) and NF-κB mRNA were reduced significantly in subjects consuming GTE alone or in combination. None of the interventions significantly affected rectal acetylated histone H3 or Ki-67 expression at the protein level or plasma C-reactive protein. Effects of the combination of Brazil nuts and GTE did not differ from what would be expected from either agent alone. In conclusion, supplementation of Brazil nuts and/or GTE regulates targeted biomarkers related to CRC oncogenesis, specifically genes associated with selenoproteins (SePP), WNT signalling (β-catenin), inflammation (NF-κB) and methylation (DNMT1). Their combination does not appear to provide additional effects compared with either agent alone.